Geographies of identity in nineteenth-century Japan - Howell, David L. (University of California Press, 2005)
In this pioneering study, David L. Howell looks beneath the surface structures of the Japanese state to reveal the mechanism by which markers of polity, status, and civilization came together over the divide of the Meiji Restoration of 1868. Howell illustrates how a short roster of malleable, explicitly superficial customs--hairstyle, clothing, and personal names-- served to distinguish the "civilized" realm of the Japanese from the "barbarian" realm of the Ainu in the Tokugawa era. Within the core polity, moreover, these same customs distinguished members of different social status groups fro